The Middle East Effect : How US’ China Policy Will be Influenced - Yang, Zi (2020)
As the threat of war looms following the assassination of Iran’s General Qassem Soleimani by US drones on President Trump’s orders, many parties stand to lose, yet China may gain. What are the implications for the US’ China policy?